The Potential of Fast-Growing Tree Species in Biomass and Soil Organic Carbon Stock and Its Implications for Climate Change Mitigation in Western Ethiopia - Semere, Mihert; Dejene, Tatek; Befikadu, Elizabeth; Kidane, Berhane; Bahiru, Tinsae (Program Pascasarjana Universitas Sriwijaya, 2024)
Plantations of fast-growing tree species are important in climate change mitigation efforts because of their enormous potential for carbon storage and the potential affected mainly by tree species type and composition, which influence particular carbon pools in the system. This study estimates biomass and soil organic carbon (SOC) under selected fast-growing tree species in Ethiopia's Diksis district, Oromia region. Major parameters, height (H) and diameter at breast height (DBH), were measured in permanently sampled plots (9mx9m) with three replications to evaluate the biomass carbon stock of selected species. Soil samples (0–15 and 15-30 cm) were also collected to determine soil organic carbon (SOC) and bulk density. Above and below-ground biomass (AGB) and (BGB) were calculated using the site and species-specific allometric equations, and SOC was analysed using appropriate procedures in the laboratory. The results showed that the highest total biomass carbon stock was recorded for Eucalyptus globulus (5.7Mg C ha-1), and the lowest was recorded for Eucalyptus grandis (1.2 Mg C ha-1). Amongst the studied tree species, the highest and lowest mean total soil organic carbon (SOC) was recorded for Eucalyptus saligna (60 Mg C ha-1) and Eucalyptus viminalis (35.4 Mg C ha-1), respectively. The study also revealed that plantation sites could enhance carbon stock accumulation in biomass and soil organic carbon. Hence, considering that incorporating fast-growing tree species in plantations is helpful in climate change mitigation strategies is a preeminent approach beyond their economic values.